Deconstructing tissue engineered trachea: Assessing the role of synthetic scaffolds, segmental replacement and cell seeding on graft performance. (15th January 2020) - Dharmadhikari, Sayali; Liu, Lumei; Shontz, Kimberly; Wiet, Matthew; White, Audrey; Goins, Andrew; Akula, Himani; Johnson, Jed; Reynolds, Susan D.; Breuer, Christopher K.; Chiang, Tendy
Abstract: The ideal construct for tracheal replacement remains elusive in the management of long segment airway defects. Tissue engineered tracheal grafts (TETG) have been limited by the development of graft stenosis or collapse, infection, or lack of an epithelial lining. We applied a mouse model of orthotopic airway surgery to assess the impact of three critical barriers encountered in clinical applications: the scaffold, the extent of intervention, and the impact of cell seeding and characterized their impact on graft performance. First, synthetic tracheal scaffolds electrospun from polyethylene terephthalate / polyurethane (PET/PU) were orthotopically implanted in anterior tracheal defects of C57BL/6 mice. Scaffolds demonstrated complete coverage with ciliated respiratory epithelium by 2 weeks. Epithelial migration was accompanied by macrophage infiltration which persisted at long term (>6 weeks) time points. We then assessed the impact of segmental tracheal implantation using syngeneic trachea as a surrogate for the ideal tracheal replacement. Graft recovery involved local upregulation of epithelial progenitor populations and there was no evidence of graft stenosis or necrosis. Implantation of electrospun synthetic tracheal scaffold for segmental replacement resulted in respiratory distress and required euthanasia at an early time point. There was limited epithelial coverage of the scaffold with and without seeded bone marrow-derived mononuclear cells (BM-MNCs). We conclude that synthetic scaffolds support re-epithelialization in orthotopic patch implantation, syngeneic graft integration occurs with focal repair mechanisms, however epithelialization in segmental synthetic scaffolds is limited and is not influenced by cell seeding. Statement of significance: The life-threatening nature of long-segment tracheal defects has led to clinical use of tissue engineered tracheal grafts in the last decade for cases of compassionate use. However, the ideal tracheal reconstruction using tissue-engineered tracheal grafts (TETG) has not been clarified. We addressed the core challenges in tissue engineered tracheal replacement (re-epithelialization and graft patency) by defining the role of cell seeding with autologous bone marrow-derived mononuclear cells, the mechanism of respiratory epithelialization and proliferation, and the role of the inflammatory immune response in regeneration. This research will facilitate comprehensive understanding of cellular regeneration and neotissue formation on TETG, which will permit targeted therapies for accelerating re-epithelialization and attenuating stenosis in tissue engineered airway replacement. Graphical abstract: Image, graphical abstract